MANAJEMEN PEMBIAYAAN PENDIDIKAN DALAM MENINGKATKAN MUTU LULUSAN DI MADRASAH TSANAWIYAH SWASTA DARUL AMAN - Amalia, Tiara; Munastiwi, Erni; Chairozi, Fachri (STKIP Pesisir Selatan, 2025)
This type of research is included in the category of qualitative research. This research was carried out at MTsS Darul Aman, Aceh Besar Regency, Aceh Province. Based on the results of research, education financing management has been implemented through three main stages: planning, implementation, and evaluation. In the planning stage, the school prepares an annual budget plan based on operational needs which includes infrastructure, teacher honorarium, learning activities, and educational quality development. The preparation of this budget is carried out in a participatory manner, involving the head of the madrasah, the treasurer, and the school committee. At the implementation stage, funds are used according to the budget plan that has been set. The school strives to maintain transparency and accountability in the use of funds, especially BOS funds and community donations. Meanwhile, in the evaluation stage, MTsS Darul Aman conducts periodic reviews of budget realization and the effectiveness of the use of funds. This evaluation is carried out by the school management team together with the committee, with the aim of ensuring that each financing really contributes to improving the quality of education. Overall, the implementation of education financing management at MTsS Darul Aman has been proven to support the creation of a more effective and efficient educational process. A well-structured and monitored financial management system is one of the important factors in encouraging better quality of education in this madrasah.